2008
DOI: 10.1007/s11373-008-9251-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sense morpholino oligonucleotide assay shows critical involvement for NF-κB activation in the production of Wnt-1 protein by HepG2 cells: oncology implications

Abstract: The link of proto-oncogenic protein Wnt-1 production with NF-kappaB activation has been functionally demonstrated in PC12 cells, a rat pheochromocytoma cell line of neural crest lineage, while it is not yet verified in human cells. The link can be indirectly supported in our previous report that functional proteomics identifies enhanced expression of NF-kappaB-associated Wnt-1 production in human hepatocellular carcinoma tissues. This study aimed to further validate this link in human cells using anti-sense st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Anti-sense morpholino oligonucleotide assay shows critical involvement for NF-jB activation in the production of Wnt-1 protein by HepG2 cells: oncology implications The present study [21] is to validate the previous finding by functional proteomics that Wnt-1 enhances the expression of NF-jB in human hepatocellular carcinoma tissues. By using anti-sense morpholino oligonucleotides(ONs) targeting pre-mRNA sequences of human p50 and p65 subunits of NF-jB as well as Wnt-1 genes, it revealed that the three ONs inhibited NF-jB activation in HepG2 cells and decreased Wnt-1 production.…”
Section: Bone Marrow Transplantation For Cholestasissupporting
confidence: 56%
“…Anti-sense morpholino oligonucleotide assay shows critical involvement for NF-jB activation in the production of Wnt-1 protein by HepG2 cells: oncology implications The present study [21] is to validate the previous finding by functional proteomics that Wnt-1 enhances the expression of NF-jB in human hepatocellular carcinoma tissues. By using anti-sense morpholino oligonucleotides(ONs) targeting pre-mRNA sequences of human p50 and p65 subunits of NF-jB as well as Wnt-1 genes, it revealed that the three ONs inhibited NF-jB activation in HepG2 cells and decreased Wnt-1 production.…”
Section: Bone Marrow Transplantation For Cholestasissupporting
confidence: 56%
“…Enhanced expression of nuclear factor-nBassociated Wnt-1 protein has been identified in a large proportion of HCC specimens with HBV and/or HCV infection (18). The nuclear factor-nB -P50 subunit has been shown to bind to the promoter of the Wnt-1 gene by chromatin immunoprecipitation assay (24). All evidence highly suggests that Wnt-1 plays an important role in HBV-and/or HCV-related hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in activation of Wnt/β-catenin signaling may also be secondary to activation of GPC3, NF-kB, GSK-3β, ERK1/2 and co-activator of β-catenin, i.e. FHL2 [36,42,46]. The activation of β-catenin signaling may trigger the activation of other signaling pathways to induce the development of hepatoblastoma, including inhibition of TNF-α-dependent apoptosis, increase in the secretion of epithelial growth factor and formation of complex of with YAP-1 protein [40,47,51].…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation assay revealed the direct binding of NF-kB-p50 to the Wnt-1 promoter region. Accordingly, it may be suggested that the activation of NF-kB may increase the production of Wnt-1, which triggers the activation of Wnt/β-catenin to induce the development of hepatoblastoma [46].…”
Section: Nuclear Factor κ-Light-chain-enhancer Of Activated B Cellsmentioning
confidence: 99%
See 1 more Smart Citation